2018
DOI: 10.1111/jcpe.12860
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric changes following ridge preservation or spontaneous healing and early implant placement with simultaneous guided bone regeneration

Abstract: Irrespective of the treatment modality and the healing period, part of the ridge contour was lost. Early implant placement after ridge preservation without additional GBR resulted in a more stable ridge contour after implant placement compared to controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…A study by Naenni and co‐workers (Naenni et al, ) performed GBR procedures simultaneously with implant placement to treat buccal dehiscencies or fenestration type defects, using either a native collagen membrane or and titanium‐reinforced non‐resorbable membrane. Although the number of completely covered defects was not reported, the percentage of defect resolution (85% with a resorbable membrane and 90.7% with a non‐resorbable membrane) was significantly higher than the values that were obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Naenni and co‐workers (Naenni et al, ) performed GBR procedures simultaneously with implant placement to treat buccal dehiscencies or fenestration type defects, using either a native collagen membrane or and titanium‐reinforced non‐resorbable membrane. Although the number of completely covered defects was not reported, the percentage of defect resolution (85% with a resorbable membrane and 90.7% with a non‐resorbable membrane) was significantly higher than the values that were obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, alveolar ridge preservation techniques (ARP) have been proposed to, at least to a certain extent, overcome this resorption process. Although evidence shows that these ARP have their benefit in limiting the resorption process, they do not totally overcome this problem (Araújo, Silva, Mendonça, & Lindhe, 2015;Naenni et al, 2017;Temmerman et al, 2016). The application of particulate xenogenic or allogenic materials covered with an absorbable collagen membrane or rapidly absorbable collagen sponge seems to be associated with the most favourable outcomes in terms of horizontal ridge preservation (Avila-Ortiz, Chambrone, & Vignoletti, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with some reported studies in canine, the unfavorable alveolar bone atrophy at horizontal and vertical dimensions in Blank group was detected in our study regarding micro-CT measurements. [41,42] As shown in Table 1 and 2, the collapse of hard tissues with no treatment applied was mainly appeared at coronal and middle part horizontally and both buccal/lingual sides vertically. In particular, at both time-points, all grafting materials greatly reduced the dimensional diminutions of the alveolar ridge, which indicated all grafting materials we used in this study shared a similar capacity regarding the maintenance of alveolar ridge.…”
Section: Discussionmentioning
confidence: 99%
“…However, T2DM patients often face the challenge of atrophic alveolar bone width at implant sites [3]. The minor and moderate atrophic ridge often requires horizontal bone augmentation by guided bone regeneration (GBR)with the combination of bone graft materials and barrier membranes [4]. It is reported that the hyperglycemia impacts the clinical effect of dental implants [5].…”
Section: Introductionmentioning
confidence: 99%